Occluded and Budded Autographa californica Nuclear Polyhedrosis Virus: Immunological Relatedness of Structural Proteins - Volkman, Loy E. (1983)
The immunological relatedness of the structural proteins of the budded and occluded phenotypes of Autographa californica nuclear polyhedrosis virus was examined by reciprocal immunoblotting and by in situ peroxidase-antiperoxidase staining of virus-induced cell surface and intracellular antigens with antisera to both phenotypes. The molecular weights (MWs) of major structural proteins of both phenotypes that reciprocally cross-reacted were 92,500, 78,000, 62,500, 54,000, and 42,000. A highly immunogenic, major structural protein of the occluded phenotype of 46,000 MW was not recognized by antiserum to the budded phenotype, and a major structural protein of the budded phenotype, 48,000 MW, was not recognized by antiserum to the occluded phenotype. Both the budded and occluded phenotypes contained a protein of 33,500 MW that comigrated with polyhedrin (the matrix protein) and reacted with antiserum and monoclonal antibody to polyhedrin. Evidence was obtained for the apparent antigenic relatedness of proteins of different MWs from the budded and occluded phenotypes, possibly indicative of different processing of some proteins for the two phenotypes. Antiserum to the occluded phenotype recognized virus-induced cell surface antigens, indicating antigenic similarities between the occluded phenotype and envelope proteins of the budded phenotype. Antiserum to the budded phenotype recognized viral proteins produced before the appearance of cytopathic effect, whereas antiserum to the occluded phenotype did not.